Modalities of choice a delegate according to the executive decree 18-199 - Chreiet, Fodil; Rebahi, Mostafa (Journal of Human Sciences, 2021)
The algerian legislature has entrusted this task to the authority responsible for the local public service. They are obliged to perform competition and advertising, which allows the largest number of competitive clients to be brought in and achieved through the competition demand formula. The exception which allows these two procedures to be neglected, is the form of mutual consent if the cases mentioned in the executive Decree 18/199 are present. The delegated authority shall establish a committee called the Selection of offer’s Committee, which shall be charged with proposing a candidate in the normal and exceptional case. It is undertaking its work in stages to select the best candidate to propose to the official of the authority delegated to issue the provisional local public facility delegation which is rebuttable becomes final.